Analysis of the type material of Navicula brachysira Brébisson with the description of Brachysira sandrae, a new raphid diatom (Bacillariophyceae) from Iles Kerguelen (TAAF, sub-Antarctica, southern Indian Ocean) - van De Vijver, Bart (Phytotaxa, 2014)
During a study of the freshwater diatom flora of some hot springs on the sub-Antarctic Kerguelen Islands, an unknown Brachysira species was observed. Detailed morphological analysis using both light and scanning electron microscopy observations revealed sufficient morphological differences to separate this species as Brachysira sandrae sp. nov. The new species belongs to the complex of taxa around B. brebissonii. The type material of Navicula brachysira, most likely the type of B. brebissonii, was studied to reveal its morphological ultrastructure. The new species is compared with B. brebissonii and with similar Brachysira taxa worldwide.